MORPHOTECTONIC STUDY OF THE BROADER AREA OF THESSALONIKI FOR THE CARTOGRAPHY OF NEOTECTONIC FAULTS - ΖΕΡΒΟΠΟΥΛΟΥ Α.; ΠΑΥΛΙΔΗΣ Σ. (Bulletin of the Geological Society of Greece, 2005)
At this paper studied the neotectonic active faults of the broader area of Thessaloniki with morphotectonic criteria. We have studied three main faults of Anthemounta, Asvestophori and Pylaia - Panorama with the contribution of cartography, digital elevation models, drainage patterns, and the morphotectonic indices like drainage basin asymmetry, mountain front sinuosity, knick points and stream length-gradient index. Those faults show elements of activity.